Pembinaan Anak Autis Di Sekolah Menengah Kejuruan Negeri (SMKN) 4 Padang - Marta Suhendra (Fakultas Tarbiyah dan Keguruan UIN Imam Bonjol Padang, 2015)
Children with autism at Vocational High School 4 Padang has some achievements both in class and the level of West Sumatra. children with autism at SMK 4 Padang been the first winner in its class and champion race Graphic Design West Sumatra level. With all their flaws, children with autism are capable of achievement beat friends in a normal class background. This research uses descriptive method with qualitative approach is a case study that describes the facts and the reality of actual and accurate information on the state of the field. Data were collected using observation and interview techniques. Based on this study it can be concluded that the success of children with autism can not be separated from the coaching is done guidance and counseling teachers, parents, teachers, friends of children with autism and the cooperation between parents and teachers. Cooperation that teachers with parents explained to the school environment on the existence of autistic children in SMKN 4 Padang, responding to the presence of children with autism and understand the behavior of children with autism. The success of children with autism gain achievements in the classroom and the level of West Sumatra can not be separated from the coaching role of parents who never gave up her lead even accompany their children to school on the morning after school. Tutor and counseling teacher always discuss with the teachers of subjects in the classroom of children with autism, about the development of the behavior of children with autism, children with autism learn and how to solve problems caused by the behavior of children with autism.